Digitalisation and poverty in Latin America: a theoretical review with a focus on education - Plaza de la Hoz, Jesús; Espinosa, Zaida; Camilli, Celia (Humanities & Social Sciences Communications, 2025)
This theoretical review/metatheory examines different theoretical approaches to digitalisation. With a focus on education, it analyses how the digitalisation of Latin American populations in vulnerable contexts is understood in 87 documents published by Latin American institutions between 2000 and 2022 that met the inclusion criteria. An inductive coding analysis of their theoretical perspectives on ICT and digitalisation was conducted, yielding four categories as results: a tendency toward (1) a humanistic model of digitalisation, (2) with a social focus, (3) a sociocultural perspective, and (4) a communitarian-substantialist understanding of ICT. The implications of these theoretical perspectives for education are discussed in terms of the aims and expectations placed upon digitalisation and can serve as a theoretical basis for public educational policies seeking to advance development in Latin America, understood in human, not just economic, terms.
Keywords: digitalisation; vulnerability; digital education; Latin America; metatheory; JCR; Scopus